Effect of paternal age on clinical outcomes of in vitro fertilization-embryo transfer cycles - Gao, Xinyan; Li, Xiao; Wang, Fanfan; Cai, Wen; Sun, Shihu; Lu, Shaoming (Frontiers in Endocrinology, 2024)
This study aimed to investigate the impact of paternal age > 40 years on clinical pregnancy and perinatal outcomes among patients undergoing in vitro fertilization treatment. Methods: We selected 75 male patients (aged > 40 years) based on predefined inclusion and exclusion criteria. Propensity score matching was performed in a 1:3 ratio, resulting in a control group (aged ≤ 40 years) of 225 individuals. Various statistical tests, including the Mann-Whitney U test, Chi-square test, Fisher's exact test, and binary logistic regression, were used to analyze the association between paternal age and clinical outcomes.We found no statistically significant differences in semen routine parameters, clinical pregnancy outcomes, and perinatal outcomes between paternal aged > 40 and ≤ 40 years. However, in the subgroup analysis, the live birth rate significantly decreased in those aged ≥ 45 compared to those aged 41-42 and 43-44 years (31.25% vs. 69.23% and 65%, respectively; all p < 0.05).Additionally, the clinical pregnancy rate was significantly lower among those aged ≥ 45 than among those aged 41-42 (43.75% vs. 74.36% ; p=0.035).Paternal age ≥ 45 years was associated with lower live birth and clinical pregnancy rates.